Training on Making Crafts from Perca Fabric to Improve the Economy of PKK Manimbahoi Village - Bakri, Muhammad; Hasyim, Hasyim (Advances in Community Services Research, 2024)
Purpose: This study aimed to integrate environmental education into school curricula to enhance environmental literacy, awareness, and sustainable behaviors among students and teachers. Research Design and Methodology: The study employed a multi-phase methodology, including needs assessment, curriculum development, teacher training, student engagement activities, mentoring, and monitoring. The project was implemented through comprehensive workshops for teachers, hands-on experiential learning activities for students, and continuous mentoring and assessment. Findings and Discussion: Results from pre- and post-intervention assessments indicated significant improvements in environmental knowledge and awareness among participants. Students displayed a deeper understanding of environmental issues such as climate change, biodiversity loss, and pollution, and exhibited positive shifts in attitudes and behaviors towards environmental conservation. Teachers reported increased confidence and competence in integrating environmental topics into their teaching practices, facilitated by professional development sessions covering contemporary environmental issues and pedagogical strategies. Implications: The study found that experiential learning activities, such as nature walks and school gardens, were particularly effective in fostering student engagement and retention of environmental knowledge. Additionally, the involvement of local environmental organizations and community members played a crucial role in reinforcing positive behavioral changes through social learning and community involvement. However, challenges such as limited resources and variability in teacher preparedness were identified, suggesting the need for ongoing support and resource allocation.